Rubber Materials R&D and Consulting Facility feasibility study - Almazar, Victor Emmanuel; Juan, Franztoni; Lim, Erica
The feasibility on the establishment of the Rubber Materials R & D and Consulting Facility aims to provide the Philippines with its very first Research and Development Facility for rubber materials. Eventually, it aims to improve the quality to locally produced rubber products by offering testing services and other experiments that would improve the production and utilization of rubber in the country. The main target market for this facility is the members of an association), which are mostly located around the Quezon City area and is relatively close to the facility, under the rubber industry called Philippines Rubber Industries Association (PRIA), currently has 50 members and this is further broken down into the tire manufacturers/suppliers/retreaders, automotive parts, industrial parts, and sporting goods manufacturers, footwear manufacturers, and the latex product manufacturers. It was found that majority of the manufacturing companies produces automotive parts, industrial parts, and sporting goods. Thus, the study will focus on the larger portion of the market because this will make up most of the demand. A projected sales forecast was made for 5 years of operation. The facility is made up 3 main laboratories namely the Raw Materials Characterization Laboratory, Raw Materials and Rubber Processing Laboratory, and the Mechanical Testing Laboratory. Tests in the Raw Materials Characterizations Laboratory are mostly used to identify the physical and compositional characteristics of raw materials and the results are mostly used to assess the processability of the raw materials before production. The Raw Materials and Rubber Processing Laboratory is used to test for alternative raw materials that can be used in rubber processing and production. Finally, the Mechanical Testing Laboratory is used to assess the qualities of finished products which as the tires and automotive parts. The facility is to be located at the UPD DMMME building inside the UP Campus, Diliman, Quezon City. Personnel or manpower for the company is computed to the most optimal number such that it will be able to cater the demands of the customers. The facility's Php 7,000,000.00 capitalization will be financed through loan and equity. Php 5,000,000.00 will be loaned to build and furnish the facility, the Php 2,000,000.00 will be raised from the owners and investors. The facility will profit by the second year of operation and will be able to start paying their debts by the third year. NPV by Year 5 is Php 13,205,885.97.